Do patients bypass rural hospitals? Determinants of inpatient hospital choice in rural California - José J. Escarce; Kanika Kapur (University College Dublin, UCD School of Economics, 2009)
Rural hospitals play a crucial role in providing healthcare to rural Americans, a vulnerable and underserved population; however, rural hospitals have faced threats to their financial viability and many have closed as a result. This paper examines the hospital characteristics that are associated with patients choosing rural hospitals, and sheds light on the types of patients who depend on rural hospitals for care and, hence, may be the most impaired by the closure of rural hospitals. Using data from California hospitals, the paper shows that patients were more likely to choose nearby hospitals, larger hospitals, and hospitals that offered more services and technologies. However, even after adjusting for these factors, patients had a propensity to bypass rural hospitals in favor of large urban hospitals. Offering additional services and technologies would increase the share of rural residents choosing rural hospitals only slightly.
hdl:10197/1007
Keywords: 330; Rural hospitals; Hospital choice; Rural health